The role of small heat shock proteins in parasites - Pérez-Morales, Deyanira (Cell Stress Chaperones, 2015)
The natural life cycle of many protozoan and helminth parasites involves exposure to several hostile environmental conditions. Under these circumstances, the parasites arouse a cellular stress response that involves the expression of heat shock proteins (HSPs). Small HSPs (sHSPs) constitute one of the main families of HSPs. The sHSPs are very divergent at the sequence level, but their secondary and tertiary structures are conserved and some of its members are related to α-crystallin from vertebrates. They are involved in a variety of cellular processes. As other HSPs, the sHSPs act as molecular chaperones; however, they have shown other activities apparently not related to chaperone action. In this review, the diverse activities of sHSPs in the major genera of protozoan and helminth parasites are described. These include stress response, development, and immune response, among others. In addition, an analysis comparing the sequences of sHSPs from some parasites using a distance analysis is presented. Because many parasites face hostile conditions through its life cycles the study of HSPs, including sHSPs, is fundamental.